2018
DOI: 10.1371/journal.pone.0204346
|View full text |Cite
|
Sign up to set email alerts
|

Epac1 protects the retina against ischemia/reperfusion-induced neuronal and vascular damage

Abstract: We had previously reported that exchange protein for cAMP 1 (Epac1) reduced inflammatory mediators in the retina of mice and in retinal endothelial cells (REC). Since ischemia can induce retinal damage potentially through activation of inflammatory cascades, we hypothesized that Epac1 would protect the retina against neuronal and vascular damage after exposure to ischemia/reperfusion (I/R). We used Epac1 floxed and endothelial cell specific Epac1 knockout mice for this work. We exposed them to ischemia for 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Previous studies have linked upregulation of inflammatory responses in diabetic and IR-injured retinas to the formation of degenerate capillaries [9,11,13]. In the present study, consistent with the ability of ADAM17 to regulate inflammatory responses, we found a reduction in leukocyte adhesion in the ischemic retinas of mice lacking endothelial ADAM17.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have linked upregulation of inflammatory responses in diabetic and IR-injured retinas to the formation of degenerate capillaries [9,11,13]. In the present study, consistent with the ability of ADAM17 to regulate inflammatory responses, we found a reduction in leukocyte adhesion in the ischemic retinas of mice lacking endothelial ADAM17.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with retinal neuronal cell loss, the IR-injured retina displays reduced thickness of the ganglion and nuclear cell layers [5,7]. More recently, several research groups reported that IR also recapitulates vascular impairments observed in the diabetic retina such as loss of vascular barrier function and capillary degeneration [9][10][11][12]. Notably, neuronal cell loss in the IR-injured retina precedes vascular capillary degeneration [9].…”
Section: Introductionmentioning
confidence: 99%
“…This study is in line with previous work showing that activation of Epac leads to apoptosis in cortical neurons and Epac1 deletion abolishes 3-nitropropionic acid–induced neuronal apoptosis ( Suzuki et al, 2010 ). Interestingly, while we found that Epac1 plays a pathologic role in RGC injury, a recent study showed that deleting Epac1 in endothelial cells accelerated retinal neuronal injury and capillary degeneration after ischemic injury ( Liu et al, 2018 ). This discrepancy suggests that Epac1 may exert different functions in different cell types.…”
Section: Discussionmentioning
confidence: 79%
“…HMGB1 has been linked to the NLRP3 inflammasome in macrophages 13. Since we have also reported that both HMGB1 and NLRP3 are increased in REC,11,20 we wanted to investigate mechanisms of activation of NLRP3 in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The Epac1 floxed mice were bred with the cdh5-Cre mice to generate conditional knockout mice in which Epac1 is eliminated in vascular endothelial cells. At 3 months of age, Epac1 floxed and Epac1 Cre-Lox mice were used for these experiments 20,21. Euthanasia was performed with drug overdose followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%